EFFECT OF PH, IONIC CONCENTRATION AND SPECIES ON THE ABSORPTION OF WATER BY HYDROGEL BIONANOCOMPOSITS CONSTITUTED FROM CMC/PAAm/ LAPONITE RDS - Garcia, Joao A. F. [UNESP]; Moura, Marcia R. de [UNESP]; Aouada, Fauze A. [UNESP] (Soc Brasileira Quimica, 2019)
The objective of this paper was to study the effect of pH. concentration and ionic species on the water absorption of the bionanocomposite hydrogels based on carboxymethylcellulose polysaccharide and laponite nanoclay. Bionanocomposite hydrogels were obtained via free radical polymerization. It was possible to observe that the swelling degree (Q) and kinetic properties were strongly influenced, and controlled, by the presence and quantity of ionic species, decreasing their water uptake when compared to the same values obtained in distilled water. Furthermore. the addition of nanoclay decreased the water uptake sensibility of the hydrogel in ionic media. It was also observed that the presence of the nanoclay decreased the Q(eq) distilled water values from 32.5 g to 22.5 g g(-1). The pKa variation of the bionanocomposites was a good indication of the possible interaction of the nanoclay-polymeric chains. The possibility of the control of water absorption (velocity and quantity) whereas these nanocomposites are pH- and salt-responsive may potentiate their application in agriculture. Agronomical studies are in progress. which can confirm its applicability in this area.
Keywords: nanoclay; swelling degree; kinetic properties; carboxymethylcellulose; pKa